PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN SIMULASI KOMPUTER TERHADAP HASIL BELAJAR MATERI KESETIMBANGAN KIMIA - Fitriah, Leny (Hydrogen: Jurnal Kependidikan Kimia, 2019)
This research uses factorial design 2 x 2. The sample in this research is the students of IKIP Kimia Mataram Chemistry study program that follow the Basic Chemistry 2 course in the even semester of academic year 2013/2014 with 2 homogenously distributed classes. The sample was taken by cluster random sampling technique. One class consists of 21 students who were taught inquiry led by using computer simulation and other class consists of 22 students with guided Inquiry. The research data are low learning result and high level learning result on chemical equilibrium material measured by using test instrument choice and essay test with content validation each 80,6% and 91,7%. The measurement of the reliability of questions was obtained from Cronbach’s Alpha formula with a value of 0.73 for multiple choice tests and 0.914 for the essay test. Data analysis using ANOVA Two Ways test. The result of the research shows that: (1) Low learning result of under guided class students in using computer simulation is higher than guided inquiry class without computer simulation; (2) Higher student learning result in guided inquiry class using computer simulation higher than guided inquiry class without computer simulation. So it can be concluded that guided inquiry learning using computer learning can student improve learning outcomes in chemical equilibrium material.